High-temperature stable and highly active/selective supported NiCoMgCeOx catalyst suitable for autothermal reforming of methane to syngas - Choudhary, Vasant R.; Mondal, Kartick C.; Mamman, Ajit Singh (Journal of Catalysis, 2005)
Low-surface-area, macroporous, zirconia-haffnia-supported NiCoMgOx and NiCoMgCeOx (Ni/Co/Mg/Ce = 1/0.2/1.2/0.0 or 1.2) catalysts, precalcined at high temperature ( 1400 degrees C for 4 h), showed both high activity (> 98% conversion) and selectivity ( > 95%) in the catalytic partial oxidation of methane (CPOM) to syngas. Their performance remained unchanged even after they were subjected to higher temperature (> 2000 degrees C for 30 min) or a number of high-temperature (> 2000 degrees C) shocks, due to their direct exposure to an oxyacetylene flame. The supported NiCoMgCeOx, however, showed superior performance in the steam and CO2 reforming reactions because of its much higher lattice oxygen mobility. Hence it is more suitable for the autothermal reforming of methane. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: autothermal reforming of methane; Catalyst; catalytic partial oxidation of methane; CO2 reforming of methane; high-temperature stable supported NiCoMgCeOx catalyst; steam reforming of methane; zirconia-haffnia-supported NiCoMgCeOx catalysts; zirconia-haffnia-supported NiCoMgOx